How Proponents and Opponents Influence Achievement Motivation: The Role of the Anticipated Emotions of Other People - Bilson Simamora (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2021)
There are countless studies about the influence of other people’s emotions on individuals' behavior. However, the influence of proponents' and opponents' future emotions on achievement motivation remains unclear. This study aims to fill this gap. Therefore, departing from the emotional intelligence theory, the author materializes the anticipated emotions of other people concept and tests it using a static group experimental design with success and failure scenarios, involving 203 participants chosen judgmentally. When reminded of the proponents' joyfulness caused by their success, the Mann-Whitney U test with normal approximation, supported by the Monte Carlo estimation, shows that the mastery-avoidance, performance-approach, and performance-avoidance goals of the experimental group are enhanced. Whereas, when reminded that they would be envied and make the opponents feel distressed, the performance-approach goals are improved. In the failure scenario, when the participants were directed to the proponents' distress, as a response to their failure, the four components of the achievement goals are increased: mastery-approach, mastery-avoidance, performance-approach, and performance-avoidance. However, the opponents' joyfulness, anticipated as a malicious schadenfreude to the participants' failure, is only successful in stimulating the performance-avoidance goals. A Bayesian estimate with 5,000 times bootstrapping reveals that self-efficacy mediates the influence of the proponents' anticipated joyfulness on the mastery-approach fully, and on the performance-approach goals in a complementary way. Complementary mediation is also apparent in the impact of the proponents' distress on the mastery-approach and mastery-avoidance goals. Above all, love for the proponents is more potent than hatred from social environments for increasing the achievement motivation. Further research is encouraged to replicate this study with different social behavior.